An Analysis of Capital Expenditure Financing on the Operations of Private Hospitals (A Case of Suburban Medical Centre) - Kanazache, Eusebius (Midlands State University, 2017)
The Zimbabwe Private Healthcare sector has been under capital distress and the researcher’s interest in the under invested sector of the economy prompted this research. The research focused on analyzing capital expenditure financing techniques on the operations of private hospitals (a case study of Suburban Medical Centre). Suburban Medical Centre has been experiencing shortages of funds to finance the acquisition of medical equipment thus the hospital is operating with obsolete and inadequate medical equipment. This has led to outsourcing of some procedures which require complex equipment and this has led to a decline in the reported revenue between the years 2012-2014. Literature from journals, text books and other publications was used for this study. Descriptive research design was used and both questionnaires and interviews were implemented so as not to confine respondents to a set of answers given on a questionnaire. The data was presented on tables, graphs and pie charts. It was highlighted in the research that financing challenges being faced are as a result of the inability to access debt, prevailing economic situation and the nature of the industry. The research outlined the following best practices for financing capital expenditure; leasing, bank loans, mortgage and the use of retained earnings. A summary, recommendations and conclusion were made and the researcher suggested areas for further study.